ANALISIS TRANSAKSI E-COMMERCE MELALUI JARINGAN MEDIA SOSIAL MOBILE - Rayung Wulan (Sosio e-Kons, 2015)
Internet development now aday become big and used very in public places easly. This facility provides in many kind of provider that makes user comfortable and secured. The application develop together with thedevelopment of internet user. The more aplication makes e –commerce change the sales pattern, by based on desktop at first become significant change with social media, operated easily throught blackberry mesangger, facebook, whatsap, line etc. E-commerce is a commercial and internet privatisation which increase rapidly this couple of years that make digital infrastructure provide efissient tools for communication, information changes and commerce to be a new media which is interesting in social media mobile net. E-commerce has become a need for a new saler or a saler who has involued long in commerce business. All aspect of commerce now has based in mobile, where ever and where ever that can be acsess with an easly application offered by a good internet. Social media that has been used by E-commerce transaction is blackberry mesangger, facebook, whatsap, in society they get transaction easily without any concern that the three social media can be tracked down easily. Keyword : Transaction, E-commerce, Media social mobile